Active Current Mirrors for Low-Voltage Analog Circuit Design - Miguez, Matias (2017)
In this work, active current mirrors using sensing resistors and a pass transistor in a feedback loop will be examined in detail. First, several non-idealities in this family of circuits, such as offset, noise, output impedance, or bandwidth, are addressed, showing no performance degradation under certain circumstances. Then, the design and measurement results of a 10-μ A (nominal) active current mirror that can operate down to just 80 mV voltage drop are presented. Finally, two simple amplifier stages using classic and active current mirrors are compared, the latter operating almost at a third of the supply voltage. It is possible to conclude that active current mirrors can be a very valuable building block for low-voltage analog circuits.